(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: The concept of the banking sector development is multi-dimensional, and it is difficult to establish a single description for it because it is an interconnected process that encompasses increases in the number and quality of banking services. Objective: The major purpose of the study is to examine the impact of bank-specific factors on the banking sector development in Nepal Method: The study applied the vector error correction model (VECM) technique with economic time series data ranging from 1995 to 2020. The study was based on co-integration analysis to determine the long-run equilibrium relationship between the model’s variables. Banking sector development is measured by the arithmetic average of the normalized values of banking depth, banking efficiency, and banking stability. Result: The study reveals that banking trade has a positive and significant influence on the banking sector’s development in line with theoretical predictions. Electronic banking and liquidity have a positive and statistically significant role to explain banking sector development in Nepal. In addition, it demonstrates that non-performing loans has a negatively and significantly influenced banking sector development whilst branch network has a marginally negative but insignificant impact on banking sector development. Conclusion: The major conclusion of the study is that there is a long-term equilibrium relationship between bank-specific variables and banking sector development. The dynamic causality of VECM reveals that banking trade, non-performing loans, electronic banking, and liquidity are statistically significant which indicates strong explanatory power to explain banking sector development in Nepal. Recommendation: This study recommends for policymakers as it sheds light on the importance of raising deposits and lending policies and focused on electronic banking. The financial institution authorities should be implied to build systems and skills in liquidity management, assets and liability management, and branch networking management to enhance the banking sector development.